Phytochemical And Biological Activity Studies On Garcinia Atroviridis Griff. Ex T. Anders. - Tan, Wen Nee (2013)
The volatile oil of the fruit of Garcinia atroviridis Griff. ex T. Anders. was isolated by hydrodistillation and analysed by capillary GC and GC-MS, using three columns of different polarity. The oil was dominated by sesquiterpenoids, with the most abundant components being (-)-β-caryophyllene (23.8 %), β-caryophyllene alcohol (15.6 %) and α-humulene (10.7 %). Three of the volatile constituents, β-caryophyllene alcohol (68), ginsenol (70) and (1S,2S,5S,8S)-4,4,8-trimethyltricyclo[6.3.1.01,5]dodecan-2-ol (71) were synthesized and isolated by preparative GC for authentication purposes.